Initiation of a cell line from turbot (Scophthalmus maximus L.) - Fernández-Puentes, Carmen; Novoa, Beatriz; Figueras Huerta, Antonio (In Vitro Cellular & Developmental Biology - Animal, 1993)
2 pages Peer reviewed